Developing a new clinical governance framework for chronic diseases in primary care: an umbrella review - Walter Ricciardi; Gianfranco Damiani; Alessandra Buja; Vincenzo Baldo; Mark H Ebell; Roberto Toffanin; Mirko Claus (BMJ Open)
Objectives Our goal is to conceptualise a clinical governance framework for the effective management of chronic diseases in the primary care setting, which will facilitate a reorganisation of healthcare services that systematically improves their performance.Setting Primary care.Participants Chronic Care Model by Wagner et aland Clinical Governance statement by Scally et alwere taken for reference. Each was reviewed, including their various components. We then conceptualised a new framework, merging the relevant aspects of both.Interventions We conducted an umbrella review of all systematic reviews published by the Cochrane Effective Practice and Organisation of Care Group to identify organisational interventions in primary care with demonstrated evidence of efficacy.Results All primary healthcare systems should be patient-centred. Interventions for patients and their families should focus on their values; on clinical, professional and institutional integration and finally on accountability to patients, peers and society at large. These interventions should be shaped by an approach to their clinical management that achieves the best clinical governance, which includes quality assurance, risk management, technology assessment, management of patient satisfaction and patient empowerment and engagement. This approach demands the implementation of a system of organisational, functional and professional management based on a population health needs assessment, resource management, evidence-based and patient-oriented research, professional education, team building and information and communication technologies that support the delivery system. All primary care should be embedded in and founded on an active partnership with the society it serves.Conclusions A framework for clinical governance will promote an integrated effort to bring together all related activities, melding environmental, administrative, support and clinical elements to ensure a coordinated and integrated approach that sustains the provision of better care for chronic conditions in primary care setting.